INTRODUCTION OF A NEW FORMULA FOR THE ASSESSMENT OF A NEW ECOLOGICAL PARAMETER, DOMINANCE VALUE INDEX - DWIVFDI, BRJESH K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Parasitic ratio viz relative abundance, relative frequency, relative density and dominance value index of Tylenchus filiformis and Tylenchorhynchus brassicae around Citrus sinensis, Psidium guajava and Zizyphus jujuba at 3 different vertical depths was analysed for the first time in the present study. The results have indicated that maximum DVI of the parasites was observed after rains in the upper strata of soil, while in the summer in the lower surface of soil.